Corrosion and Low Temperature Degradation of 3Y-TZP dental ceramics under acidic conditions. Issue 15 (December 2020) - Nowicka, A.; El-Maghraby, H.F.; Švančárková, A.; Galusková, D.; Reveron, H.; Gremillard, L.; Chevalier, J.; Galusek, D.
Abstract: Due to its excellent properties, yttria-stabilized tetragonal zirconia ceramics (Y-TZP) are considered to be an appropriate choice for advanced dental applications. However, the long-term surface stability of these materials in a humid environment is still a matter of discussion. In the present work, two commercial and one in-house prepared 3Y-TZP ceramics were studied. The materials stability and durability were evaluated in the light of their behavior against long-term corrosion under low acidic pH (up to 265 days) and Low Temperature Degradation (LTD). The extent of corrosion and LTD was monitored by determining the content of monoclinic zirconia at the surfaces by X-Ray Diffraction. The obtained results show that leaching of yttrium from the 3Y-TZP tested materials takes place. Nonetheless, there is no significant impact of yttrium loss on the vulnerability to LTD of corroded samples in the conditions of this work.